2021
DOI: 10.31234/osf.io/zqe9s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stock market as a casino: Associations between stock market trading frequency and problem gambling

Abstract: The stock market should be a unique kind of casino, where the average person wins money over time. However, previous research shows that excessive stock market trading can contribute to financial losses --- just like in any other casino. While gambling research has documented the adverse consequences of problem gambling, there has been comparatively less behavioral finance research on the correlates of excessive stock market trading. This study aimed to document whether excessive stock trading was positively a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(50 reference statements)
0
5
0
1
Order By: Relevance
“…Similarly, Dorn and Sengmueller (2009) finds that investors who self-reportedly enjoy both gambling and investing exhibit significantly higher portfolio turnover rates than those who do not, and that the enjoyment sourced from both activities helps explain excessive trading behavior. Mosenhauer et al (2021) and Liu et al (2022) provide additional evidence to the link of gambling motives and excessive trading. The latter find that gambling preferences and the perceived information advantage of investors dominate all other surveyed motives in explaining excessive trading.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, Dorn and Sengmueller (2009) finds that investors who self-reportedly enjoy both gambling and investing exhibit significantly higher portfolio turnover rates than those who do not, and that the enjoyment sourced from both activities helps explain excessive trading behavior. Mosenhauer et al (2021) and Liu et al (2022) provide additional evidence to the link of gambling motives and excessive trading. The latter find that gambling preferences and the perceived information advantage of investors dominate all other surveyed motives in explaining excessive trading.…”
Section: Introductionmentioning
confidence: 94%
“…Williams et al (2022) reported the result of a logistic regression predicting past year speculation and found that higher gambling frequency was the strongest predictor (OR = 1.65), and higher PGSI was also a significant predictor (OR = 1.07). In an article using a Prolific sample of individuals who had experience with gambling and current investments (Mosenhauer et al, 2021), risk for problem gambling predicted high trading frequency (i.e. turn over) over and above the other predictors (i.e.…”
Section: Problem Gambling Measuresmentioning
confidence: 99%
“…Second, they often provide users with prompts and notifications to entice frequent portfolio checking and further trading, reducing inertia through inaction (Zweig, 2020). Furthermore, there appears to be a trend towards the "gamblification" of trading, with the aim of transforming it into an addictive activity similar to gambling (Mosenhauer et al, 2021). The influence of social media, bringing individuals who acquire large gains from random lucky investments into the spotlight, while those with similar strategies but who incur losses not being as well publicized, might lead to investors mimicking inefficient behavior.…”
Section: Real-world Investment Decisionsmentioning
confidence: 99%